Haemorrhoids: piling on the agony. Issue 4 (25th July 2018) - Siddiqui, Muhammed; Mohamed, Said; Ashrafian, Hutan
Abstract : Perianal disease is often considered 'assumed knowledge' among clinicians but is generally poorly understood. This article gives an overview of haemorrhoidal disease and its management options.